Mālojī va Śahājī : carcātmaka caritra - Khare, Vāsudeva Vāmanaśāstrī, 1858-1924 (SAMP early 20th-century Indian books project, 1920)
On the life of Maloji Bhonsle, 1550-1606 and Shahji Bhonsle, 1594-1664, Maratha kings.